Editorial Says on Malaysian Journal of Sport Science and Recreation (MJSSR) / Dr. Tan Chee Hian - Tan (Dr.), Chee Hian (Faculty of Sports Science and Recreation, 2011)
Malaysian Journal of Sport Science and Recreation (MJSSR) was grown from the early Dean of Faculty of Sports Science and Recreation (FSR) UiTM, Professor Dr Muhd Kamil Ibrahim and it is a continuous affort and conjoined vision of all other FSR deans since 2001. The first journal’s editor-in-chief was Associate Professor Dr Kwame Ampofo-Boateng, who moved from FSR for career advancement. However, MJSSR is apparently considered as the one’s issue of Malaysian’s setting of Sports Science and Recreation (broadly-defined) journal. It is hoped that this journal would be an avenue for high quality academic research papers aimed in sharing ideas, findings and reflections of academic world in Malaysia or abroad.